Boundary Versions of the Worpitzky Theorem for Two-Dimensional Continued Fractions - Kuchmins’ka, Kh. Yo. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
For a two-dimensional continued fraction another generalization of the Worpitzky theorem is proved and the limit sets are proposed for Worpitzky-like theorems in the case where the element sets of the twodimensional continued fraction are replaced by their boundaries.